Denial of the access to the Spanish nationality by poligamy: case-law analysis - Castellanos Ruiz, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The Judgment of the Audiencia Nacional Court (Sala de lo Contencioso-administrativo) of September 11, 2017 denies the acquisition of the Spanish nacionality to a citizen of the Republic of Guinea legally married to several women in his country of origin, due to the lack of “sufficient degree of integration in the Spanish society” (Art. 22.3 CC), confirming the statement of the DGRN (administrative Spanish authorities). In the existing jurisprudence this indeterminate legal concept is defined, although some rules do regulate it as well. From this analysis, we conclude that although polygamy is valid according to the national law of the foreign individual (Art. 9.1 CC), it constitutes a reality against the fundamental principles of Spanish marital law. So the foreign law that allows a person affected by hindrance to marriage (Art. 46.2 º CC) can get married with another person, violates the Spanish public policy rule (Art. 12.3 CC). However, the courts consider that the circumstances of each case should be analyzed to verify that the foreign individual effectively exercises polygamy, and if not, he should access to the Spanish nationality, in opposition to the DGRN opinion, which denies the access to the Spanish nationality because the applicant chooses polygamy in the foreign marriage certificate, although he has not really exercised it. In any case, the legal effects of polygamous marriages in Spain are also studied, when the polygamous applicant acquires the Spanish nationality through fraud or deception.
Keywords: Spanish nacionality; poligamy; sufficient level of integration in the Spanish society; public policy rule